(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Survey nurses’ knowledge about implementing technical procedures for injecting drugs to patients at Vinh Medical University Hospital in 2023. Research method: Cross-sectional descriptive study with analysis of over 60 nurses working in patient care in inpatient departments at Vinh Medical University hospital from March 2023 to November 2023. Results: The rate of nurses with knowledge of safe injections was 33.3%. Among them, there are still a number of criteria with low achievement rates such as: The proportion of nurses who answered correctly about the technique of disinfecting the injection site accounted for 61.7%, the proportion of nurses who said that the angle of intramuscular injection was 60 - 90 degrees is 60%, the proportion of nurses who think that the sharp object container with the full signal line is 3/4 of the container is 51.71%, the proportion of nurses who answer correctly about the angle of intravenous injection is 55%, the percentage of nurses who correctly answered the method of using alcohol cotton to disinfect the injection site was 66.7%. Conclusion: The rate of nurses gaining knowledge about safe injections is low. Among them, there are still a number of criteria with a low rate such as: technique of disinfecting the injection site, the angle of intramuscular injection with the signal line on the sharp object container, the angle of intravenous injection, and the use of alcohol cotton to disinfect the site injection.